Collaboration in Altavas, Aklan during the Japanese occupation the case of Dr. Roque R. Mayor - Arboleda, Leah S. .
This is the study of Dr. roque Mayor's role during the Japanese occupation of Altavas, Aklan, what are the causes of their collaboration and their contributions in Altavas' local history., This study describe the nature of collaboration, identified the factors that caused the Mayors collaborate with the Japanese authorities during their occupation of the town and analyzed the significance of Dr. Roque Mayor's collaboration. Dr. Roque Mayor collaborated with the Japanese to minimize the sufferings of civilians of Altavas. He showed cooperation with the Japanese and on the other hand, he gave vital information relative to the activities of the Japanese . To ensure his safety and the civilians, he requested the guerillas not to raid the town. With his collaboration, no further killings had occurred in their ten-month occupation of the town.